2010
DOI: 10.2169/internalmedicine.49.2714
|View full text |Cite
|
Sign up to set email alerts
|

A Pleuro-Peritoneal Communication through the Diaphragm affected with Lymphangioleiomyomatosis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…62,66 The diaphragmatic LAM lesion can generate pleuro-peritoneal communication through LAMassociated lymphangiogenesis rather than an anatomical defect of the diaphragm. 67 On the other hand, Morimoto et al reported that chylorrhea from swollen vessels on the right diaphragm was observed by thoracoscopy in a Japanese LAM patient who had right chylothorax. 61 Chyloptysis can occur due to stasis of the lymph flow with a reflux of chyle into the tracheobronchial tree (Fig.…”
Section: Clinical Manifestations Related To Lymphatic Involvementsmentioning
confidence: 98%
See 1 more Smart Citation
“…62,66 The diaphragmatic LAM lesion can generate pleuro-peritoneal communication through LAMassociated lymphangiogenesis rather than an anatomical defect of the diaphragm. 67 On the other hand, Morimoto et al reported that chylorrhea from swollen vessels on the right diaphragm was observed by thoracoscopy in a Japanese LAM patient who had right chylothorax. 61 Chyloptysis can occur due to stasis of the lymph flow with a reflux of chyle into the tracheobronchial tree (Fig.…”
Section: Clinical Manifestations Related To Lymphatic Involvementsmentioning
confidence: 98%
“…Chylous pleural effusion, ascites, and chyloptysis, are often contaminated with red blood cells (Fig. 1), 67 thus suggesting the presence of bloodlymphatic vessel shunts. Abundant lymphatic vessels with few blood vessels in LAM lesions may indicate that VEGF-Dmediated lymphangiogenesis suppresses angiogenesis in LAM lesions.…”
mentioning
confidence: 99%
“…Figure 1 presents a flowchart showing the complete breakdown of the steps used in the identification of appropriate studies [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,…”
Section: Resultsmentioning
confidence: 99%
“…The question of whether the PE was transudate or exudate was only addressed in 14 cases, and all corresponded to the latter. PF triglyceride levels were reported in 20 cases [23,25,29,32,37,45,47,49,60,63,74,77,81,82,83,84,87,88,91,101], and all had values higher than 110 mg/dl (range 190-4,600 mg/dl). The presence of chylomicrons was only specified in 3 cases [46,83,101].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation